Tanzania Economic Update, December 2013 : Raising the Game--Can Tanzania Eradicate Extreme Poverty? - World Bank (Washington, DC, 2014)
The special focus of this fourth economic update is as much a concern for policymakers as for ordinary citizens. This economic update discusses a bold new way of lessening extreme poverty by transferring cash directly to the most vulnerable people. In Tanzania, the success of a similar program piloted by the Tanzania Social Action Fund (TASAF), which includes conditional cash transfers as well as public works for productive infrastructure, is also very encouraging as shown by an independent evaluation. Although cash transfers are promising, as this update discusses, there are risks associated with implementation on a large scale. It will be essential to ensure effective targeting and sound monitoring. And the decision to scale up needs to be embedded in strategic thinking about medium-term fiscal sustainability. The economic update also discusses the state of the economy more broadly. Strong and stable economic growth and gradually declining inflation have been the hallmarks of Tanzania's recent economic performance. Tanzania needs to strike the right balance between making large capital investments and maintaining fiscal discipline. Tanzania needs to maintain fiscal discipline and continue to keep the country's debt and debt-service at acceptable levels to consolidate the gains achieved over the past decade. In this context, the report is organized in two parts: part one is the state of the economy; and part two is money to people: can conditional cash transfers make a difference?